Composite metal oxide semiconductor based photodiodes for solar panel tracking applications - Al-Ghamdi, Ahmed A.; Dere, A.; Tataroglu, A.; Arif, Bilal; Yakuphanoğlu, Fahrettin; El-Tantawy, Farid; Farooq, W. A. (Elsevier Science Sa, 2015)
The Zn1-xAlxO:Cu2O composite films were synthesized by the sol gel method to fabricate photodiodes. The transparent metal oxide Zn1-xAlxO:Cu2O thin films were grown on p-Si substrates by spin coating technique. Electrical characterization of the p-Si/AZO:Cu2O photodiodes was performed by current-voltage and capacitanceeconductanceevoltage characteristics under dark and various illumination conditions. The transient photocurrent of the diodes increases with increase in illumination intensity. The photoconducting mechanism of the diodes is controlled by the continuous distribution of trap levels. The photocapacitance and photoconductivity of the diodes are decreased with increasing Cu2O content. The series resistance-voltage behavior confirms the presence of the interface states in the interface of the diodes. The photoresponse properties of the diodes indicate that the p-Si/Zn1-xAlxO-Cu2O diodes can be used as a photosensor in solar panel tracking applications. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Sensors; Photodiode; Sol gel method